Telephone message - Addison, Christopher Addison, Viscount, 1869-1951 ; Brook, Charles Wortham, 1901-1983 ; Midgley, Harry, d. 1957; EKK
010-0060-001 9th November, 1936. 3.55 p.m. TELEPHONE MESSAGE - given by Dr. Brook's Secretary. Dr. Brook has received a wire to-day from Dr. Addison reading as follows :- "Two Belfast men, McMahon and Boyd serving with Scottish Medical Unit have been captured by Franco's troop at Madrid. Use influence with Foreign Office immediately to ensure their safety." (Signed) MIDGLEY. (Dr. Addison's Secretary to Dr. Brook.) Dr. Brook says can Dr. Morgan see Sir Walter Citrine about it, and see if some overtures can be made to the Foreign Office. EKK. 292/946/10/63